Efektifitas Tata Kelola Barang Milik Negara (BMN) di Lingkungan Kementerian Agama - Lubis, Ervy Alinda (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2023)
The complexity of issues related to the management of State Property Asset (BMN) at the Ministry of Religion is a crucial problem that has an impact on the achievement of strategic objectives to improve the quality of governance in the field. Explicitly, the ineffectiveness of BMN management is related to disorganized administration, physical inventory, and legality aspects which are reflected in the results of the evaluation, Strategic Plan, and evaluation of the implementation of Bureaucratic Reform of the Ministry of Religion. This research aims to produce recommendations for optimizing BMN governance policies within the Ministry of Religion. A mixed method approach was used with three data collection techniques, namely document studies, interviews related to governance mechanisms, and a survey with purposive sampling of 830 respondents from the Ministry of Religion employees. The results of the study stated that the value effectiveness of BMN governance was simultaneously less effective with a score of 3.36 (poor) on a scale of 1-5 with a minimum effective category passing grade of obtaining a score of 3.41 (Good). Five indicators serve as parameters for the effectiveness of BMN management, two indicators are still problems that cause BMN management to be less effective, namely aspects of supervision and integrity with a score of 3.11 and effectiveness of application support in BMN management with a score of 3.33. The other three aspects have been running effectively, namely transparency (3.44), specifications procurement use of goods (3.44), and capacity of BMN managers (3.52).